Mahmud Darwısh and Marcıl Khalıfa: Art and Commitment - Møller Sørensen, Søren (Danish Yearbook of Musicology, 2016)
The Lebanese composer, musician and singer Marcıl Khalıfa (b. 1950) has for decades been a central figure in Middle Eastern music. Early in his career he became acquainted with the poetry of the Palestinian poet Mahmud Darwısh (1941–2008) and set some of his most beloved early poems in music. Some of the resulting songs such as ila ummi (To my Mother) and jawaz safar (A Passport) are still beloved and often played and heard. This article takes issue with political and aesthetic positions of these two artists. Both take their point of departure in the political left and both are strongly committed to issues of modern Arab national identity and particularly to the Palestinian issue. But in their works, in their public statements, and in the critical discourses on them we also find a negotiation of the relation between political commitment and societal responsibility and modern artists’ rightful claim on artistic autonomy. The article traces this negotiation in Western as well as Arab sources.